Memórias em jogo: futebol, seleção brasileira e as Copas do Mundo de 1950 e 1954 - Banchetti, Luciano Deppa (2011)
Is there a proper space for memories and stories about football? Is there a memory of the football world which becomes more widespread? In seeking answers to these questions, it is possible to perceive that despite all the diversity and importance of the phenomenon in several regions of the country, we can, in contradiction, identify the predominance of a single memory of the football in Brazil, widely spread through a variety of means. This demonstrates that there is a tendency to look for uniqueness, to establish a vision of the past that tries to constantly repeat some data and, at the same intensity, ends in silecing other opinions or data, thus generalizing an idea intended to be the only one representing what would be a model of the Brazilian football. Thus, considering how intense is the relationship between football and memory, the main objective of this paper is to discuss the building of an idea on the past of the football world, aiming to analyse the tracjectory of some members of this activity in the cities of Rio de Janeiro and São Paulo, in moments such as the participation of the Brazilian National Team in the first post-war World Cups, more precisely the period of abstinence from the Jules Rimet Trophy race in the 1940s to the busy days of the games in the World Championships: 1950 held in Brazil and 1954 held in Switzeland. Through the analysis of several sources, such as newspapers (especially those of the Casper Libero Foundation), magazines and memories, we tried to emphasize the expectations, the euphoria and disappointment among many participants of different groups directly involved with the football world at that time government authorities, sport officials, players, press, fans. Narratives which have contributed to make the football this social phenomenon of enormous significance in the present days